Calculation of the Scattering Amplitude of A Nucleus in the Presence of the Yukawa Potential - L. Nickhah; A. A. Rajabi; F. Pakdel (Department of Physics, Sebelas Maret University, 2015)
The scattering amplitudes are obtained from the phase shifts for a spherically symmetric potential using the D-dimensional Schrödinger equation and the partial wave method. Plots show that the real and imaginary parts of the scattering amplitude are almost similar behavior.